Correlation of integrated pulmonary index with clinical observation in unilateral and bilateral spinal anaesthesia in geriatric patients - Mermer, Damla; Turan, Guldem; Koksal, Ceren; Tas, Berna Ayanoglu; Karadogan, Firdevs; Akgun, Nur (International Journal of Research in Medical Sciences, 2016)
Background: In present study, we aimed to determine the role of integrated pulmonary index (IPI) in monitorising geriatric cases that have spontaneous ventilation under unilateral and spinal block during partial hip prosthesis and total knee arthroplasty. Methods: 24 patients who were over 65 years of age and with ASA I-IV, femoral neck fracture, intertrochanteric fracture and in whom gonarthros had developed were simply randomised into two groups. Values of blood pressure, pulse rate (PR), SPO2, EtCO2, respiratory rate (RR), IPI were recorded. Unilateral spinal block was administered with 7.5 mg, 0.5% bupivacaine and 25 mcg fentanyl in Group I and with 12.5 mg 0.5% bupivacaine and 25 mcg fentanyl in Group II. Values were recorded in intervals of 5 and 15 minutes and continued to be recorded from the moment of cement application. Preoperative mask ventilation or intubation need was recorded. Results: For EtCO2, bilateral spinal block scores at post-cement 15 minutes; postop 5 minutes were found to be high providing that they were within the clinically normal limits compared to the unilateral scores. A correlation between IPI and SpO2, EtCO2, respiratory rate, pulse rate was identified. In both groups, IPI was found to be in normal range and a correlation was identified through clinical observation. Conclusions: IPI might be the sole numerical value in early identification of clinical correlation and respiratory failure. For the IPI monitor is small and easy to be handled along with its screen that shows many parameters together makes the device be easily used.